Development of electrochemical biosensor based on SnO2-nanofiber with enhanced electron transfer of redox biomolecule - Alim, Samiul (2019)
Electrochemical biosensors are highly desirable for the monitoring of H2O2, glucose, cholesterol, cancer biomarkers, infectious diseases, etc. But the development of enzymatic electrochemical biosensors is oppressed with great challenges like the lack of good electronic coupling and electrical contact between the active site of the used redox protein/enzyme and the electrode surface. Hence, a great deal of effort has been devoted by using nanofiber (NF) of SnO2 as nanomaterial in biosensor to deal with this challenge. Thus, the main theme of this dissertation pertains to highlighting the critical roles that are played by this nanomaterial when this is applied in the development of electrochemical biosensors by immobilizing different redox proteins or enzymes. The SnO2-NFs used in this research was synthesised by electrospinning technique from the tin precursor. The synthesized SnO2-NF increases the efficiency of biomolecule loading due to its high surface area. The morphology of the nanofiber was evaluated by field emission scanning electron microscopy (FESEM) and energy-dispersive X-ray (EDX) spectrometer was used for evaluating the sterility of the synthesized nanofiber. For this research project, an amperometric H2O2 biosensor was designed and fabricated firstly based on the immobilization of horseradish peroxidase (HRP) enzyme with NF of SnO2 onto the surface of glassy carbon electrode (GC) by using chitosan, which exhibited fast response with lower detection limit of 0.3 M (S/N=3). The fabricated HRP/SnO2-NF/Ch/GC biosensor showed linearity ranges between the concentration of 10 to 120 M H2O2. To evaluate the performance of the modified SnO2 nanofiber in biosensor, a HRP based H2O2 biosensor was then designed and fabricated, whereas, the NFs of SnO2 was polymerized with polyaniline (PANI) and HRP enzyme was immobilized with this PANI/SnO2 onto the surface of GC. The fabricated HRP/PANI/SnO2-NF/Ch/GCE biosensor displayed a linear amperometric response towards the H2O2 concentration range from 10 to 80 M with a detection limit of 0.133 M (S/N=3). A bienzymatic glucose biosensor was then designed and fabricated based on the polymerized SnO2-NF via co-immobilization of glucose oxidase (GOx) and horseradish peroxidase (HRP) with this by using chitosan onto glassy carbon electrode. This biosensor was fabricated to evaluate the potentiality of SnO2-NF in the development of bienzymatic biosensor. The HRP-GOx/PANI/SnO2-NF/Ch/GC biosensor displayed a linear amperometric response towards the glucose concentration range from 10 to 110 M with a detection limit of 1.8 M (S/N = 3). Also the anti-interference activity was investigated. Finally, SnO2-NF with Carbon nanotubes (CNT) and chitosan was used together for the fabrication of another novel H2O2 biosensor to evaluate the synergic effect of SnO2-NF with other nanomaterial in biosensing. A redox protein (Hemoglobin) was immobilized with CNT/SnO2-NF nanocomposite by using chitosan on the surface of GC. The fabricated Hb/CNT/SnO2-NF/Ch/GC electrode exhibited linearity to the H2O2 concentration in a wide range of 10 to 200 M and the lower detection limit was 30 nM (S/N=3). A direct electron transfer between the active center of redox protein/enzyme and the electrode surface was established because of using this nanofiber and all the biosensors reported in this work exhibited excellent selectivity with stability, reproducibility and repeatability.